Reactive oxygen species-induced impairment of endothelium-dependent relaxations in rat aortic rings: protection by methanolic extracts of phoebe grandis - Lau, Yeh-Siang; Subramaniam, G.; Hamid, A.H.A.; Murugan, D.; Mustafa, Mohd Rais (2011)
Introduction: Metastatic lesions to the oro-facial region may be the first evidence of dissemination of an unknown tumour from its primary site. Case